Map of Mexico, Central America, and the West Indies. - Mitchell, S. Augustus, Jr. (Samuel Augustus) ([S.A. Mitchell], 1872)
Map shows late nineteenth century geography, cities, and towns in Mexico, Central America, and the West Indies. Includes distances from the Port of New Orleans to various ports in Mexico, Central America, Cuba, and Jamaica. Insets: "Map of the Bermuda Islands," "Map of the Panama Railroad," "Map of the Island of Jamaica," and "Map of the Sandwich Islands." Relief shown by hachures and spot heights. Scale [ca. 1:11,700,000].